The initial momentum of the system is,
![p_i=m_1u_1+m_2u_2](https://img.qammunity.org/2023/formulas/physics/college/1gmt8x4y25pwwrgu2qb14c5hmsw9pyvt36.png)
The final momentum of the system is,
![p_f=m_1v_1+m_2v_2](https://img.qammunity.org/2023/formulas/physics/college/8no0kualirzeb4zjjuvislutjgp9ko7tz5.png)
According to conservation of momentum,
![p_i=p_f](https://img.qammunity.org/2023/formulas/physics/college/e7rj8yeigkhgmt4s6ul64ny08zwwhw91ko.png)
Plug in the known values,
![m_1u_{1_{}}+m_2u_2=m_1v_1+m_2v_2](https://img.qammunity.org/2023/formulas/physics/college/lk26jac1iwtlwyqz30fu7rw6mf9p43d5xm.png)
Substitute the known values,
![\begin{gathered} (1230kg)(14.6m/s)+(1278kg)(13m/s)=(1230kg)(13.6m/s)+(1278kg)v_2 \\ 17958\text{ kgm/s+}16614\text{ kgm/s=}16728\text{ kgm/s+}(1278kg)v_2 \\ v_2=\frac{34572\text{ kgm/s-}16728\text{ kgm/s}}{1278\text{ kg}} \\ =13.96\text{ m/s} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/avc29q3jpsp7hk88fz11ku8z3zy1bw4lby.png)
The initial kinetic energy of the system is,
![K=(1)/(2)m_1u^2_1+(1)/(2)m_2u^{2^{}}_{2^{}}](https://img.qammunity.org/2023/formulas/physics/college/ka387binnkb276n4x8hj2zgv53zkk36pqs.png)
The final kinetic energy of the system is,
![K^(\prime)=(1)/(2)m_1v^2_1+(1)/(2)m_2v^{2^{}}_{2^{}}](https://img.qammunity.org/2023/formulas/physics/college/tx184xmtc06b8djo7env7pb8sgrhklzy69.png)
The change in kinetic energy of the system is,
![\Delta K=K^(\prime)-K](https://img.qammunity.org/2023/formulas/physics/college/ass7ljbspyplhk9bxh8diuxfgcbul9csx1.png)
Plug in the known expressions,
![\begin{gathered} \Delta K=(1)/(2)m_2v^2_2+(1)/(2)m_1v^2_1-(1)/(2)m_2u^2_2-(1)/(2)m_1u^2_1 \\ =(1)/(2)m_2(v^2_2-v^2_1)+(1)/(2)m_1(v^2_1-u^2_1) \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/r01ipdmb5lmc3o14jyj0rzlgpc65odqqa3.png)
Substitute the known values,
![\begin{gathered} \Delta K=(1)/(2)(1278kg)((13.96m/s)^2-(13m/s)^2)+ \\ (1)/(2)(1230kg)((13.6m/s)^2-(14.6m/s)^2) \\ =(639\text{ kg)(}194.88m^2s^(-2)-169m^2s^(-2))+(615\text{ kg)(}184.96m^2s^(-2)-213.16m^2s^(-2)) \\ =(639\text{ kg)(}25.88\text{ }m^2s^(-2))(\frac{1\text{ J}}{1\text{ kg}m^2s^(-2)})+(615\text{ kg)(}-28.2m^2s^(-2))(\frac{1\text{ J}}{1\text{ kg}m^2s^(-2)}) \\ =16537.32\text{ J-}17343\text{ J} \\ =-805.68\text{ J} \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/5bmx8gxjus0u8ida2438um6txdxdoieyro.png)
Therefore, the change in kinetic energy of the system is -805.68 J.